Association of expression of inflammatory response genes and DNA repair genes in colorectal carcinoma. Issue 4 (April 2019) - Germini, Demétrius Eduardo; Franco, Maria Isete Fares; Fonseca, Fernando Luiz Affonso; de Sousa Gehrke, Flávia; da Costa Aguiar Alves Reis, Beatriz; Cardili, Leonardo; Oshima, Celina Tizuko Fujiyama; Theodoro, Thérèse Rachell; Waisberg, Jaques
Inflammation is an important etiological factor of colorectal carcinoma and may be related to colorectal carcinoma growth and proliferation. This study aimed to verify whether the presence of chronic inflammation represented by tumor necrosis factor-α, interleukin-2, interleukin-6, and interleukin-10 gene expression is related to hMLH1, hMSH2, hMSH6, and PMS2 gene expression and the corresponding protein levels of these genes from the DNA repair system. A total of 83 patients were operated on for curative or palliative colorectal carcinoma. Expression of the inflammatory response genes tumor necrosis factor-α, interleukin-2, interleukin-6, and interleukin-10 as well as expression of the hMLH1, hMSH2, hMSH6, and PMS2 genes of the DNA repair system (mismatch repair) and the expression levels of the corresponding mismatch repair proteins were measured in neoplastic tissue by reverse transcription polymerase chain reaction and immunohistochemistry, respectively. Associations were observed between hMSH6 mRNA expression and interleukin-2 mRNA expression (p = 0.026) as well as between hMLH1 and hMSH2 gene expression and tumor necrosis factor-α gene expression (p = 0.042). Higher tissue levels of interleukin-2 and tumor necrosis factor-α gene expression were associated with lower hMSH6, hMLH1, and hMSH2 gene expression.